Studi Keragaman dan Habitat Gastropoda di Daerah Litoral Muara Sungai Ketahun Bengkulu Utara - Lilis Alifah; Bhakti Karyadi; Deni Parlindungan; Aprina Defianti; Annisa Novianti Taufik; Sutarno Sutarno (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This research aims to identify the abundance, diversity, dominance and evenness of gastropods at the mouth of the Ketahun River, North Bengkulu. The method used is the "purposive" method. The sampling location was divided into 4 (four) stations, namely in the tidal area and on the right and left in the downstream part of the estuary. The sampling technique uses transects, at each station measuring 20m. Gastropod data analysis uses the Shannon Wiener index, Simpson index, and Pielou index. The research results showed that at the mouth of the Ketahun river, 18 species of gastropods were obtained consisting of 7 genera and 3 families. The diversity index shows, a) station I has an index value of 1.81 (medium category); b) station II has an index value of 0.49 (low category); c) station III has an index value of 1.89 (medium category); d) station IV has an index value of 0.82 (low category). The dominance index shows, a) station I has an index value of 0.23 (low category); b) station II has an index value of 0.70 (medium category); c) station III has an index value of 0.19 (low category); d) station IV has an index value of 0.63 (medium category). The evenness index shows, a) station I has an index value of 0.62 (high category); b) station II has an index value of 0.17 (small category); c) station III has an index value of 0.65 (high category); d) station IV has an index value of 0.28 (small category). The most common gastropod found is the genus Clithon with a total of 1369 individuals. Abundance, diversity, dominance and evenness are determined by abiotic parameters and environmental conditions such as substrate and water quality. Keywords: Bengkulu, Gastropods, Ketahun River